Relationship between Physical Activity and Eating Patterns Toward Body Mass Index (BMI) in Nursing Students - Syahruramdhani, Syahruramdhani; Munarji, Rahmi Pratiwi (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Physical activity and eating patterns affect human health. Lack of physical activity and wrong eating patterns will increase BMI, leading to obesity and other diseases. The study aims to determine the relationship between physical activity and eating patterns toward body mass index (BMI) in nursing students. The design of the study was an observational cross-sectional study. The selection of a total of 98 respondents used the technique of a simple random sample collected with the International Physical Activity Questionnaire (IPAQ) for physical activity, eating patterns questionnaire, and measurement of BMI with digital weight scales and height meters. The statistical test used was Spearman's rank correlation. The results of this study indicated a relationship between physical activity, eating patterns and BMI, with a p-value of 0.004 and  0.003, respectively. To conclude, students had a significant relationship between physical activity and eating patterns on BMI. The nursing curriculum should emphasize the importance and benefits of physical activity and eating habits.